Crystal structure of Ruminococcus albus cellobiose 2‐epimerase: Structural insights into epimerization of unmodified sugar. Issue 7 (24th February 2013) - Fujiwara, Takaaki; Saburi, Wataru; Inoue, Sota; Mori, Haruhide; Matsui, Hirokazu; Tanaka, Isao; Yao, Min
Abstract : RaCE and X‐ray crystallography (View interaction) Abstract : ► We determined the crystal structure of Ra CE. ► We found that His184 is required for Ra CE activity. ► We proposed a new catalytic mechanism for CE involving three histidines.